Exploring the influence of market orientation and organisational structure on agribusiness firms’ innovative performance - Corchuelo-Azua, B.; Dias, Á.; Sama-Berrocal, C. (XXV APPLIED ECONOMICS MEETING, 2023)
Agribusiness shows a growing degree of competitiveness and innovation. However, the organisational mechanisms that compete for innovation and organisational performance are under-studied. This study aims to analyse the influence of market orientation and organisational structure on innovation generated in these firms. To test the conceptual model, we follow a two-step approach combining a PLS-SEM procedure with an importance-performance map analysis. The results reveal that, when compared to exploitative innovation, explorative innovation shows a stronger influence on market and financial performance of Extremaduran agribusiness firms. Furthermore, the firms’ market orientation and the existence of a formal organisational structure represent important elements to develop innovation exploration orientation.